ANALISIS KESULITAN BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA PROSES PEMBELAJARAN DARING KELAS X DI SMA NEGERI 1 KUANTAN MUDIK - Wahyu Defri Yuanda; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find an explanation of the problems raised, namely to find out the difficulty of learning corners in the online learning process for class X at SMA Negeri 1 Kuantan Mudik. The type of research is descriptive research, carried out at SMA Negeri 1 Kuantan Mudik, Jln Jendral Sudirman, Bukit Pedusunan, Kuantan Singingi Regency, Riau from April 2021 to September 2021. The sample of this study was 135 students from 203 populations. The data was taken from the instrument in the form of a questionnaire (questionnaire) containing 30 questions. From the results of the study, it was concluded that the difficulties experienced by class X students of SMA Negeri 1 Kuantan Mudik were signal technical problems and the inability to learn online in the form of an unstable network, students were less focused when the teacher explained, students were not ready in terms of learning material. Stakeholders play an important role in facilitating students in online learning and then becoming facilitators for students, especially parents who are closest to students. Implementation of learning is very influential on the learning process because it is during the implementation of learning that students can capture a material.Key Words: Learning Difficulty Analysis, Online Learning